The MOCI (Menjadi Orang Tua Cerdik) Dalam Deteksi Dini Diabetes Melitus Pada Anak Kelurahan Bojong Baru - Wahdini, Rizqa; Ellynia; Chairunisa, Ratu; Sibualamu, Khalida Ziah (Jurnal Pengabdian Kesehatan, 2024)
Background: Diabetes Mellitus (DM) poses a significant global health issue, with Indonesia ranking seventh in the world for the number of DM cases and an increasing prevalence. Objective: This community service initiative aims to enhance knowledge and skills related to early detection of diabetes in children through a community-based educational program in Bojong Baru Village, Bogor City. Methods: The implementation involved preparation, delivery of education to parents, and health assessments of children. Results: Evaluation revealed a significant increase in parental knowledge about diabetes mellitus following the educational intervention, with 70% of parents demonstrating good knowledge post-intervention compared to 30% pre-intervention. Health assessments and random blood glucose tests of children indicated that the majority were within normal ranges and had good nutritional status. These findings underscore the importance of health education for early diabetes detection and management of diabetes risk in children, as well as the effectiveness of community involvement in preventive health programs.